1981
DOI: 10.1017/s0022172400069436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selenite F, Muller-Kauffmann tetrathionate and Rappaport's medium for salmonella isolation from chicken giblets after pre-enrichment in buffered peptone water

Abstract: SUMMARYSix hundred and eighty three samples of chicken giblets were examined for salmonellas. Three hundred and forty nine of these were neck and crop specimens and 334 were combined liver and heart samples. Two hundred and ten, in all, contained salmonellas.The technique of examination included pre-enrichment in buffered peptone water at 37°C for 18 h and subculture to three enrichment media: MullerKauffmann tetrathionate, selenite F and Rappaport's magnesium chloride malachite green broth. Inocula from buffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…The findings concerning the R25 medium were confirmed by Harvey, Price & Xirouchaki (1979), Harvey & Price (1981, 1982a and Fricker, Girdwood & Munro (1983). On the other hand, Alcaide et al (1982), using RV medium with the addition of novobiocin and van Schothorst & Renaud (1983), using RV medium made with soya peptone showed that the RV medium was significantly more efficient than selenite broth or Muller-Kauffmann tetrathionate broth (MK-ISO), respectively.…”
Section: Introductionmentioning
confidence: 82%
“…The findings concerning the R25 medium were confirmed by Harvey, Price & Xirouchaki (1979), Harvey & Price (1981, 1982a and Fricker, Girdwood & Munro (1983). On the other hand, Alcaide et al (1982), using RV medium with the addition of novobiocin and van Schothorst & Renaud (1983), using RV medium made with soya peptone showed that the RV medium was significantly more efficient than selenite broth or Muller-Kauffmann tetrathionate broth (MK-ISO), respectively.…”
Section: Introductionmentioning
confidence: 82%
“…Use of BPW pre‐enrichment with faecal samples may be linked to the popularity of RV enrichment broth, which requires small inoculum volumes, or high inoculum ratios ( Harvey and Price 1980). Harvey and Price (1981) considered the need for high inoculum ratios to be an advantage when pre‐enrichment is used but, citing the example of pig faeces, a potential liability if direct inoculation with large amounts of material is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…(1999) reported that recovery of Salmonella bacteria from swine faeces enriched in TTB tended to be reduced if pre‐enrichment in BPW was used. Studies with a range of materials have commonly found RV to be superior to tetrathionate broths when compared subsequent to pre‐enrichment ( Harvey and Price 1981; Rhodes and Quesnel 1986). The nature of the source material, the prevalent serotypes in the material, and the use of direct enrichment or pre‐enrichment, were recognized to be factors likely to influence the results of studies comparing enrichment media ( Harvey and Price 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‗gold standard' for Salmonella detection in food follows a standard protocol of nonselective pre-enrichment, selective enrichment, isolation on selective agar media and biochemical and serological confirmation. Choice of enrichment broth, incubation temperature, inoculum ratio and plating media affect the Salmonella detection limit (17,34,45,51,83,84,141,143,160,193). Numerous cultivation methods that are commonly used in Salmonella surveillance and outbreak investigations vary significantly in sensitivity and specificity (30,45,63,120,164,193).…”
Section: Limitations Of International Equivalence In Product Samplingmentioning
confidence: 99%